TECHNOLOGY ACCEPTANCE IN THELITERATURE FROM 2020 TO 2024 - Molina Gonzalez, Maria del Rosario (IPHO-Journal of Advance Research in Science And Engineering, 2024)
The intensive use of technologies, devices and electronic networks not only own differences between users and non-users, but also even among those who use one ortheother same technology that eventually perfects and involves continuous learning abilities and knowledge processing and dissemination of information.The objective of the present study was to establish the reliability and validity of an instrument that measures the intention to search for information.From a non-experimental, exploratory andcross-sectional study with a non-probabilistic selection of 100 students at a public university, it is planned eight dimensions among navojoa.uson.mx which explain the information selectivity of 21%atfull.Regarding the design limits of the studysampleandthetestingof the dimensionsrecommendedin an investigation of major components in the analysisconfirmatory factor.